Deriving an Evidence-based Measure of Job Quality from the HILDA Survey - Butterworth, P; Leach, L (My University, 2010)
The Household, Income and Labour Dynamics in Australia (HILDA) survey includes twelve items that assess different psychosocial characteristics of work. However, these items are not drawn from an established scale and, therefore, we do not know the best way to combine the items, or indeed the validity of doing so. The current study uses several different statistical methods to develop measures of the psychosocial characteristics of jobs using these items. Consistent with previous research and theory, the results show that the twelve HILDA survey items reflect three key components of psychosocial job adversity: job demands and complexity, job control and job security. This factor structure was consistent across the seven waves of the survey data available for analysis. Based on the current findings, we plan to use the psychosocial job quality items to investigate the relationship between job adversity and physical and mental health over time.
Australian Social Policy Journal
Keywords: Employment; Labour market; Employment; Employment and unemployment